2021
DOI: 10.1007/s00395-021-00860-0
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte depolarization triggers NOS-dependent NO transient after calcium release, reducing the subsequent calcium transient

Abstract: Cardiac excitation–contraction coupling and metabolic and signaling activities are centrally modulated by nitric oxide (NO), which is produced by one of three NO synthases (NOSs). Despite the significant role of NO in cardiac Ca2+ homeostasis regulation under different pathophysiological conditions, such as Duchenne muscular dystrophy (DMD), no precise method describes the production, source or effect of NO through two NO signaling pathways: soluble guanylate cyclase-protein kinase G (NO-sGC-PKG) and S-nitrosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 121 publications
0
11
0
Order By: Relevance
“…Recent works in this area are not related to cell elongation. For example, in studies on isolated murine cardiomyocytes loaded with a highly specific copper dye for NO, the authors observed a single transient signal of NO production after any particular event of electrical stimulation (Mosqueira et al, 2021 ). Application of specific NOS isoform blockers or NO scavengers causes significant NO transient inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Recent works in this area are not related to cell elongation. For example, in studies on isolated murine cardiomyocytes loaded with a highly specific copper dye for NO, the authors observed a single transient signal of NO production after any particular event of electrical stimulation (Mosqueira et al, 2021 ). Application of specific NOS isoform blockers or NO scavengers causes significant NO transient inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…These aspects mentioned above were relevant owing to the possibility of independent evaluation without interference of two known pathways, through which NO exerts its effect: either via NO-sGC-PKG or post-translational modification from peroxynitrite nitrosylating thiol groups of cysteines, well-known as S-nitrosylation (SNO) ( Eu et al, 2000 ; Mosqueira et al, 2013 ) or via nitration of tyrosine rings ( Viner et al, 1999 ; Squier and Bigelow, 2000 ; Uda et al, 2020 ). Taking advantage of the standard pharmacological tools, we first used the sGC’s activator Bay41-2272 and the blocker ODQ ( Drenning et al, 2008 ; Makris et al, 2010 ; Mosqueira et al, 2021 ). Leaving aside the results of excitability parameters, the results from force-frequency and single twitch biophysical parameters showed that Bay41-2272 and ODQ induced similar effects as observed with SNAP and L-NAME, respectively, suggesting that NO would modulate force production via sGC.…”
Section: Discussionmentioning
confidence: 99%
“…Leaving aside the results of excitability parameters, the results from force-frequency and single twitch biophysical parameters showed that Bay41-2272 and ODQ induced similar effects as observed with SNAP and L-NAME, respectively, suggesting that NO would modulate force production via sGC. The next point of investigation addressed PKG, which is activated by cGMP-produced sGC, using a specific agonist [8-pCPT-cGMP Ishikawa et al (2019) , Mosqueira et al (2021) ] and a blocker (DT-3 ( Takahashi et al, 2008 )). Supporting previous results, the analysis of rheobase differed from SNAP and L-NAME, but no effect was seen in the analyses of rheobase for Bay41-2272 and ODQ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to reactive oxygen and nitrogen species, Ca 2+ -dependent RyR2 activation is physiologically regulated by phosphorylation via protein kinase A (PKA) and Ca 2+ /calmodulin-dependent kinase II (CaMKII; Niggli et al, 2013 ). Interestingly, increased RyR2 sensitivity mediated by the neuronal isoform of the nitric oxide synthase (nNOS) and CaMKII was shown to be induced by multiaxial mechanical stress during cardiomyocyte contraction ( Jian et al, 2014 ; Mosqueira et al, 2021 ). As cellular afterload response results in modulation of RyR2 activity in adult cardiomyocytes, substrates with different stiffnesses may influence signaling pathways leading to altered Ca 2+ sensitivity of RyR2s in iPSC-CMs as well.…”
Section: Discussionmentioning
confidence: 99%